Molecular response of chorioretinal endothelial cells to complement injury: implications for macular degeneration2. Issue 3 (24th December 2015) - Zeng, Shemin; Whitmore, S Scott; Sohn, Elliott H; Riker, Megan J; Wiley, Luke A; Scheetz, Todd E; Stone, Edwin M; Tucker, Budd A; Mullins, Robert F
Abstract: Age‐related macular degeneration (AMD) is a common, blinding disease of the elderly in which macular photoreceptor cells, retinal pigment epithelium and choriocapillaris endothelial cells ultimately degenerate. Recent studies have found that degeneration of the choriocapillaris occurs early in this disease and that endothelial cell drop‐out is concomitant with increased deposition of the complement membrane attack complex (MAC) at the choroidal endothelium. However, the impact of MAC injury to choroidal endothelial cells is poorly understood. To model this event in vitro, and to study the downstream consequences of MAC injury, endothelial cells were exposed to complement from human serum, compared to heat‐inactivated serum, which lacks complement components. Cells exposed to complement components in human serum showed increased labelling with antibodies directed against the MAC, time‐ and dose‐dependent cell death, as assessed by lactate dehydrogenase assay and increased permeability. RNA‐Seq analysis following complement injury revealed increased expression of genes associated with angiogenesis including matrix metalloproteinase (MMP)‐3 and −9, and VEGF‐A. The MAC‐induced increase in MMP9 RNA expression was validated using C5‐depleted serum compared to C5‐reconstituted serum. Increased levels of MMP9 were also established, using western blot and zymography. These data suggest that, in addition to cell lysis, complement attack on choroidal endothelial cells promotes an angiogenic phenotype in surviving cells. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.